1996
DOI: 10.1007/bf00389788
|View full text |Cite
|
Sign up to set email alerts
|

Serum creatine kinase enzyme levels in the early diagnosis of spermatic cord torsion

Abstract: Delay in the diagnosis of spermatic cord torsion (SCT) is still a significant cause of testicular loss in children. The aim of this experimental study was to assess the diagnostic value of serum creatine kinase (CK) in the early period following SCT. Forty male rats were assigned randomly into five similar groups: group A, control; group B, sham, right testis exposed, manipulated, and blood sampling at 6th h; group C, right SCT, blood sampling at 2nd h; group D, right SCT, blood sampling at 4th h; and group E,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It has been reported that CK and its isoenzymes have a diagnostic value in tissue ischaemia, especially in testicular torsion 2,6,27 . Serum CK levels in rats in the early period following spermatic cord torsion increased significantly before necrosis of the testicular tissue 6 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported that CK and its isoenzymes have a diagnostic value in tissue ischaemia, especially in testicular torsion 2,6,27 . Serum CK levels in rats in the early period following spermatic cord torsion increased significantly before necrosis of the testicular tissue 6 .…”
Section: Discussionmentioning
confidence: 95%
“…The deleterious effect of the toxic oxygen free radicals released during reperfusion can be ameliorated by the administration of free radical scavengers 1–4 . Malondialdehyde (MDA) is widely used as an indicator of oxidative stress induced by I/R in testicular tissue 1,5 and creatine kinase (CK) may have a diagnostic value for determining of the level of tissue ischaemia 2,6 …”
Section: Introductionmentioning
confidence: 99%
“…Receiver operating characteristic (ROC) curve comparing interleukin-6 (IL-6) and creatine phosphokinase (CPK) for discriminating epididymitis from testicular torsion with area-under-the-curve (AUC) analysis. 4,5 The source of CK-MM elevation was thought to be cremaster muscle infarction. Our study did not reproduce their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Three serologic markers of potential utility have been evaluated in previous models in the diagnosis of acute scrotum: creatine phosphokinase-MM (CPK-MM), 4,5 interleukin-6 (IL-6), 6 and interleukin-1 (IL-1). 7,8 The purpose of this study was to evaluate IL-1, IL-6, and CPK-MM in men presenting with acute scrotal pain.…”
mentioning
confidence: 99%